2014
DOI: 10.1186/1756-3305-7-177
|View full text |Cite
|
Sign up to set email alerts
|

Novel expression profiles of microRNAs suggest that specific miRNAs regulate gene expression for the sexual maturation of female Schistosoma japonicum after pairing

Abstract: BackgroundSchistosoma japonicum is one of the major causative agents of schistosomiasis. The pairing of males and females leads to female sexual maturation and maintains this mature state. However, the mechanisms by which pairing facilitates sexual maturation are yet to be investigated.MethodsParasites isolated from single- and double-sex cercariae-infected mice were analyzed by Solexa to uncover pair-regulated miRNA profiles. To reveal the biological functions of differentially expressed miRNAs among the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 52 publications
1
56
0
Order By: Relevance
“…Interestingly, bantam expression was differentially upregulated in S. mansoni females from paired infections when compared with female only infections, suggesting that it plays a role in the pairingdependent female sexual maturation (Sun et al, 2014). Contrasting roles in this process might be played by miR-1 and miR-71 which were upregulated in unpaired females (Sun et al, 2014). Both miRNAs were detected in the NEJs of F. hepatica, but only miR-71 is highly expressed.…”
Section: Ancient Metazoan and Protostome Conserved Mirnas Are The Mosmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, bantam expression was differentially upregulated in S. mansoni females from paired infections when compared with female only infections, suggesting that it plays a role in the pairingdependent female sexual maturation (Sun et al, 2014). Contrasting roles in this process might be played by miR-1 and miR-71 which were upregulated in unpaired females (Sun et al, 2014). Both miRNAs were detected in the NEJs of F. hepatica, but only miR-71 is highly expressed.…”
Section: Ancient Metazoan and Protostome Conserved Mirnas Are The Mosmentioning
confidence: 98%
“…In insects, bantam has been implicated in the regulation of cell proliferation and apoptosis and more recently it has been demonstrated to have a role in systemic growth by regulating ecdysone production (Boulan et al, 2013). Interestingly, bantam expression was differentially upregulated in S. mansoni females from paired infections when compared with female only infections, suggesting that it plays a role in the pairingdependent female sexual maturation (Sun et al, 2014). Contrasting roles in this process might be played by miR-1 and miR-71 which were upregulated in unpaired females (Sun et al, 2014).…”
Section: Ancient Metazoan and Protostome Conserved Mirnas Are The Mosmentioning
confidence: 99%
“…Among the 41 differentially expressed miRNAs in the two susceptibility host species under S. japonicum infection, four miRNAs had been identified with specific functions such as sexual maturation, embryo development, and pathogenesis of schistosomiasis. Compared with normal double-sex cercariaeinfected sourced adult worms, sja-miR-1 and sja-miR-7-5p were specifically characterized as upregulated miRNAs in single-sex cercariae developed adult worms, which demonstrated that sja-miR-1 and sja-miR-7-5p were involved in the female sexual maturation process (Sun et al 2014). And sjamiR-36-3p was suggested to play important roles in embryo development (Cai et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Among all the mappable reads, 19.5 and 22.2 % of those reads in schistosomula from Wistar rats and BALB/c mice, respectively, mapped to selected miRNAs in miRBase, and nearly 90 % of the miRNAs were between 20 and 24 nt in length, which provided abundant and essential data for further analysis (Sun et al 2014). Nearly 60 % (41/68) of the identified S. japonicum-specific miRNAs in miRBase were differentially expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Also, miRNAs are reported to regulate a variety of developmental and physiological processes in various parasites [9], including Trypanosoma brucei, Toxoplasma gondii , and Schistosoma japonicum [1012]. Some recent studies have investigated differences in miRNA expression profiles and related specific biological functions in parasite-infected hosts [13].…”
Section: Introductionmentioning
confidence: 99%